An Evaluation of the Mental Health Referrals to the Dales Living Well Team in Derbyshire - Adeel Rauf; Mark Broadhurst (BJPsych Open)
Aims: To examine the referrals in a newly established Living Well service at Dales community mental health team, Derbsyhire.